Effect of Nebulized Albuterol on Serum Lactate and Potassium in Healthy Subjects. (11th May 2016) - Zitek, Tony; Cleveland, Nathan; Rahbar, Aryan; Parker, Joshua; Lim, Chee; Elsbecker, Steven; Forred, Wesley; Slattery, David E.
Abstract: Objectives: The objectives were to determine if nebulized albuterol causes an increase in the serum lactate level compared to placebo and, secondarily, to confirm that albuterol decreases serum potassium levels compared to placebo in patients with normokalemia. Methods: This was a randomized, double‐blind, placebo‐controlled trial. Twenty‐eight healthy adult volunteers were assigned to receive either 10 mg of nebulized albuterol or placebo (nebulized saline) over 1 hour. Serum lactate was measured prior to treatment and at 30 and 70 minutes after the start of treatment. Serum potassium level was measured prior to treatment and at 70 minutes. The primary outcome was the degree of change in lactate level. The secondary outcome was the degree of change in potassium level. Results: In the 14 subjects who received albuterol, the mean increase in lactate was 0.77 mmol/L (95% confidence interval [CI] = 0.52 to 1.02 mmol/L), and the mean decrease in potassium level was 0.5 mEq/L (95% CI = −0.72 to −0.28 mEq/L). Among the subjects who received placebo, the lactate level decreased by 0.15 mmol/L (95% CI = −0.39 to 0.09 mmol/L) and there was no change in potassium level at (0.0 mEq/L [95% CI = −0.21 to 0.21 mEq/L]). These differences are statistically significant (p < 0.0001 and p = 0.003, respectively). Conclusion: Nebulized albuterol increases lactate levels and decreases potassium levels in healthy adults.